Issues and Implecation of Population on Urban Environment and Health: Evidence from India - Vijayyabasker, K.N.
The state of human health globally serves as a key indicator for the conditions of the natural environment and the success of sustainable development. Sound development is not possible without a healthy population. Many development activities affect the environment in a way that typically causes or exacerbates health problems. At the same time, a lack of development adversely affects the health of many people. Environmental pollution is one of the serious problems faced by the people in the country. Rapid population growth, industrialization and urbanization accompanied by growing number of vehicles in country are adversely affecting the environment. Though the relationship is complex, population size and growth tend to expand and accelerate these human impacts on the environment. All these in turn lead to an increase in the pollution levels. However, environmental pollution not only leads to deteriorating environmental conditions but also have adverse effects on the health of people. India is one of the most de graded environment countries in the world and it is paying heavy health and economic price for it. The present paper is an attempt to discuss the issues and implications of population on environment and health of the people.
Keywords: Sustainable development; Population; Environmental Pollution; Urbanization